Functionalized branched EDOT-terthiophene copolymer films by electropolymerization and post-polymerization “click”-reactions - Goll, Miriam; Ruff, Adrian; Muks, Erna; Goerigk, Felix; Omiecienski, Beatrice; Ruff, Ines; González-Cano, Rafael C.; Lopez Navarrete, Juan T.; Ruiz Delgado, M. Carmen; Ludwigs, Sabine (Beilstein Journal of Organic Chemistry, 2015)
The electrocopolymerization of 3,4-ethylenedioxythiophene (EDOT) with the branched thiophene building block 2,2′:3′,2″-terthiophene (3T) is presented as a versatile route to functional polymer films. Comparisons to blend systems of the respective homopolymers PEDOT and P3T by in situ spectroelectrochemistry and Raman spectroscopy prove the successful copolymer formation and the access to tailored redox properties and energy levels. The use of EDOT-N3 as co-monomer furthermore allows modifications of the films by polymer analogous reactions. Here, we exemplarily describe the post-functionalization with ionic moieties by 1,3-dipolar cycloaddition (“click”-chemistry) which allows to tune the surface polarity of the copolymer films from water contact angles of 140° down to 40°.
Keywords: band-gap engineering; “click”-chemistry; conducting polymers; electropolymerization; Raman spectroscopy; surface functionalization

(untitled) - Roncali, J. (Macromol. Rapid Commun., 2007)

(untitled) - Scharber, M. C.; Mühlbacher, D.; Koppe, M.; Denk, P.; Waldauf, C.; Heeger, A. J.; Brabec, C. J. (Adv. Mater., 2006)

(untitled) - Li, G.; Zhu, R.; Yang, Y. (Nat. Photonics, 2012)

(untitled) - Heuer, H. W.; Wehrmann, R.; Kirchmeyer, S. (Adv. Funct. Mater., 2002)

(untitled) - Sirringhaus, H. (Adv. Mater., 2005)

(untitled) - Gross, M.; Müller, D.; Nothofer, H.-G.; Scherf, U.; Neher, D.; Bräuchle, C.; Meerholz, K. (Nature, 2000)

(untitled) - Roncali, J.; Thobie-Gautier, C. (Adv. Mater., 1994)

(untitled) - Waltman, R. J.; Bargon, J.; Diaz, A. F. (J. Phys. Chem., 1983)

(untitled) - Sirringhaus, H.; Brown, P. J.; Friend, R. H.; Nielsen, M. M.; Bechgaard, K.; Langeveld-Voss, B. M. W.; Spiering, A. J. H.; Janssen, R. A. J.; Meijer, E. W.; Herwig, P.; de Leeuw, D. M. (Nature, 1999)

(untitled) - Groenendaal, L.; Jonas, F.; Freitag, D.; Pielartzik, H.; Reynolds, J. R. (Adv. Mater., 2000)

(untitled) - Wudl, F.; Kobayashi, M.; Heeger, A. J. (J. Org. Chem., 1984)

(untitled) - Havinga, E. E.; ten Hoeve, W.; Wynberg, H. (Polym. Bull., 1992)

(untitled) - Naka, K.; Umeyama, T.; Chujo, Y. (Macromolecules, 2000)

(untitled) - van Duren, J.; Dhanabalan, A.; van Hal, P. A.; Janssen, R. A. J. (Synth. Met., 2001)

(untitled) - Heinze, J.; Frontana-Uribe, B. A.; Ludwigs, S. (Chem. Rev., 2010)

(untitled) - Piron, F.; Leriche, P.; Mabon, G.; Grosu, I.; Roncali, J. (Electrochem. Commun., 2008)

(untitled) - Piron, F.; Leriche, P.; Grosu, I.; Roncali, J. (J. Mater. Chem., 2010)

(untitled) - Benincori, T.; Bonometti, V.; De Angelis, F.; Falciola, L.; Muccini, M.; Mussini, P. R.; Pilati, T.; Rampinini, G.; Rizzo, S.; Toffanin, S.; Sannicolò, F. (Chem. – Eur. J., 2010)

(untitled) - Inganäs, O.; Liedberg, B.; Chang-Ru, W.; Wynberg, H. (Synth. Met., 1985)

(untitled) - Kuwabata, S.; Ito, S.; Yoneyama, H. (J. Electrochem. Soc., 1988)

(untitled) - Funt, B. L.; Peters, E. M.; Van Dyke, J. D. (J. Polym. Sci., Part A: Polym. Chem., 1986)

(untitled) - Peters, E. M.; Van Dyke, J. D. (J. Polym. Sci., Part A: Polym. Chem., 1992)

(untitled) - Huang, H.; Pickup, P. G. (Chem. Mater., 1998)

(untitled) - Link, S. M.; Scheuble, M.; Goll, M.; Muks, E.; Ruff, A.; Hoffmann, A.; Richter, T. V.; Lopez Navarrete, J. T.; Ruiz Delgado, M. C.; Ludwigs, S. (Langmuir, 2013)

Conjugated Polyelectrolytes: Fundamentals and Applications - Liu, B.; Bazan, G. C. (Wiley-VCH, 2013)

(untitled) - Richter, T. V.; Bühler, C.; Ludwigs, S. (J. Am. Chem. Soc., 2012)

Handbook of Conducting Polymers - Skotheim, T. A.; Elsenbaumer, R. L.; Reynolds, J. R. (Marcel Dekker, 1998)

(untitled) - Seo, J. H.; Gutacker, A.; Sun, Y.; Wu, H.; Huang, F.; Cao, Y.; Scherf, U.; Heeger, A. J.; Bazan, G. C. (J. Am. Chem. Soc., 2011)

Small Organic Molecules on Surfaces - Sitter, H.; Draxl, C.; Ramsey, M. (Springer, 2013)

(untitled) - Sundaresan, N. S.; Basak, S.; Pomerantz, M.; Reynolds, J. R. (J. Chem. Soc., Chem. Commun., 1987)

(untitled) - Reynolds, J. R.; Sundaresan, N. S.; Pomerantz, M.; Basak, S.; Baker, C. K. (J. Electroanal. Chem. Interfacial Electrochem., 1988)

(untitled) - Patil, A. O.; Ikenoue, Y.; Wudl, F.; Heeger, A. J. (J. Am. Chem. Soc., 1987)

(untitled) - Patil, A. O.; Ikenoue, Y.; Basescu, N.; Colaneri, N.; Chen, J.; Wudl, F.; Heeger, A. J. (Synth. Met., 1987)

(untitled) - Ikenoue, Y.; Outani, N.; Patil, A. O.; Wudl, F.; Heeger, A. J. (Synth. Met., 1989)

(untitled) - Bäuerle, P.; Gaudl, K.-U.; Würthner, F.; Sariciftci, N. S.; Mehring, M.; Neugebauer, H.; Zhong, C.; Doblhofer, K. (Adv. Mater., 1990)

(untitled) - Visy, C.; Kankare, J.; Kriván, E. (Electrochim. Acta, 2000)

Self-Doped Conducting Polymers - Freund, M. S.; Deore, B. (John Wiley & Sons, Ltd., 2007)

(untitled) - Zotti, G.; Musiani, M.; Zecchin, S.; Schiavon, G.; Berlin, A.; Pagani, G. (Chem. Mater., 1998)

(untitled) - Binder, W. H.; Sachsenhofer, R. (Macromol. Rapid Commun., 2007)

Functional Polymers by Post-Polymerization Modification: Concepts, Guidelines and Applications - Theato, P.; Klok, H.-A. (Wiley-VCH, 2012)

(untitled) - Bu, H.-B.; Götz, G.; Reinold, E.; Vogt, A.; Schmid, S.; Blanco, R.; Segura, J. L.; Bäuerle, P. (Chem. Commun., 2008)

(untitled) - Bu, H.-B.; Götz, G.; Reinold, E.; Vogt, A.; Schmid, S.; Segura, J. L.; Blanco, R.; Gómez, R.; Bäuerle, P. (Tetrahedron, 2011)

(untitled) - Bu, H.-B.; Götz, G.; Reinold, E.; Vogt, A.; Azumi, R.; Segura, J. L.; Bäuerle, P. (Chem. Commun., 2012)

(untitled) - Sinha, J.; Sahoo, R.; Kumar, A. (Macromolecules, 2009)

(untitled) - Daugaard, A. E.; Hvilsted, S.; Hansen, T. S.; Larsen, N. B. (Macromolecules, 2008)

(untitled) - Hansen, T. S.; Daugaard, A. E.; Hvilsted, S.; Larsen, N. B. (Adv. Mater., 2009)

(untitled) - Shida, N.; Ishiguro, Y.; Atobe, M.; Fuchigami, T.; Inagi, S. (ACS Macro Lett., 2012)

(untitled) - Holze, R. (Electrochim. Acta, 2011)

(untitled) - Ak, M.; Cetişli, H.; Toppare, L. (Colloid Polym. Sci., 2012)

(untitled) - Cardona, C. M.; Li, W.; Kaifer, A. E.; Stockdale, D.; Bazan, G. C. (Adv. Mater., 2011)

(untitled) - Garreau, S.; Louarn, G.; Buisson, J. P.; Froyer, G.; Lefrant, S. (Macromolecules, 1999)

(untitled) - Louarn, G.; Buisson, J. P.; Lefrant, S.; Fichou, D. (J. Phys. Chem., 1995)

(untitled) - Capel Ferrón, C.; Ruiz Delgado, M. C.; Gidron, O.; Sharma, S.; Sheberla, D.; Sheynin, Y.; Bendikov, M.; López Navarrete, J. T.; Hernández, V. (Chem. Commun., 2012)

(untitled) - Casado, J.; Hernández, V.; Hotta, S.; López Navarrete, J. T. (J. Chem. Phys., 1998)

(untitled) - Turbiez, M.; Frère, P.; Roncali, J. (J. Org. Chem., 2003)

(untitled) - Turbiez, M.; Frère, P.; Allain, M.; Videlot, C.; Ackermann, J.; Roncali, J. (Chem. – Eur. J., 2005)

(untitled) - Kolb, H. C.; Finn, M. G.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2001)

(untitled) - Lind, J. U.; Hansen, T. S.; Daugaard, A. E.; Hvilsted, S.; Andresen, T. L.; Larsen, N. B. (Macromolecules, 2011)

(untitled) - Nicolas, M. (J. Adhes. Sci. Technol., 2008)

(untitled) - Foster, E. L.; De Leon, A. C. C.; Mangadlao, J.; Advincula, R. (J. Mater. Chem., 2012)

(untitled) - Richter, T. V.; Link, S.; Hanselmann, R.; Ludwigs, S. (Macromol. Rapid Commun., 2009)

(untitled) - Gritzner, G.; Kůta, J. (Pure Appl. Chem., 1982)

(untitled) - Segura, J. L.; Gómez, R.; Reinold, E.; Bäuerle, P. (Org. Lett., 2005)

(untitled) - Norris, B. C.; Li, W.; Lee, E.; Manthiram, A.; Bielawski, C. W. (Polymer, 2010)